Comparison of PAH mass concentrations in aerosols of the middle Adriatic coast area and central Croatia - Jakovljević, Ivana, inženjerka kemijske tehnologije (Array, 2020)
Polycyclic aromatic hydrocarbons (PAHs) are considered priority pollutants due to their distribution, persistence, bioaccumulation, and adverse effects on human health. The aim of this study was to obtain the first insight into PAHs mass concentrations bound to airborne particulate matter (PM) in the mid Adriatic coast area of Croatia, and compare them with the PAH levels in Croatia’s urban central area. Relatively low values of PAH mass concentrations were measured in the coastal area, compared to the continental urban region of Croatia impacted by increased emissions due to intensive traffic, industry, and residential heating. A high PM10 contribution of four-ring PAHs (Flu and Pyr) at Martinska site indicated that wood burning heating as well as open fire events, including waste incineration, could be important emission sources of PAHs in the mid Adriatic coast region.